Nurturing Sustainability in Toddlerhood: Investigating Preschool Teachers’ Views and Daily Practices in a Swedish Preschool - Deniz Kahriman-Pamuk; Ingrid Pramling Samuelsson (Children)
Background/Objectives: While studies suggest that young children can learn and think about sustainability, most research has focused on children aged three to five, leaving a significant gap in understanding how to engage toddlers (one to three years of age) in early-childhood education in sustainability (ECEfS). This study aims to address this gap, a crucial and often overlooked area, by investigating preschool teachers’ views of ECEfS and their daily practices for nurturing sustainability in a toddler group in a Swedish preschool. Methods: We employed a case study approach, incorporating observations, interviews, and document analysis for data collection. Qualitative techniques were used for data analysis. The research was conducted with a strong commitment to ethical considerations, including obtaining participants’ consent, ensuring confidentiality and privacy, informing them of their right to withdraw, and maintaining anonymity. Results: The findings demonstrate that the teachers possessed a solid understanding of education for sustainability and were capable of effectively implementing sustainability-related daily practices in toddler groups. By creating suitable learning environments and integrating sustainability issues into daily classroom activities, they enhanced the children’s overall learning experiences. Conclusions: This study’s findings underscore the pivotal role of educators in shaping the mindsets and behaviors of future generations, thereby supporting the long-term goals of sustainable development. By nurturing toddlers’ innate curiosity and harnessing their brains’ plasticity, educators can effectively engage toddlers in ECEfS and promote sustainable development from an early age. This study’s implications highlight the need to prioritize ECEfS during toddlerhood to realize the full potential of this critical investment in the future of our planet.